Novas dimensões da lírica de Camões - AZEVEDO FILHO, Leodegário A. de Azevedo (1979)
AZEVEDO FILHO, Leodegário A. de. Novas dimensões da lírica de Camões. Revista de Letras. Fortaleza, v.1, n. 3, 1979, p. 6-13.